Diagnostic accuracy of an in-house Scrub Typhus enzyme linked immunoassay for the detection of IgM and IgG antibodies in Laos. - Philip N D Elders; Sandhya Dhawan; Ampai Tanganuchitcharnchai; Koukeo Phommasone; Vilada Chansamouth; Nicholas P J Day; Jose A Garcia-Rivera; Jeffrey C Hertz; Mayfong Mayxay; Manivanh Vongsouvath; Audrey Dubot-Pérès; Matthew T Robinson; et al. (Public Library of Science (PLoS), 2020)
Scrub typhus is a major cause of morbidity and mortality in Southeast Asia. Diagnosis of scrub typhus is difficult due to a lack of accessible validated diagnostic tools. Despite its objectivity, the diagnostic accuracy of ELISA tests is influenced by methodological and patient factors. This study aims to evaluate the performance of a novel in-house ELISA developed in the Mahidol Oxford Tropical Medicine Research Unit (MORU) for anti-scrub typhus group IgM and IgG compared to the "gold standard" reference IFA and PCR, and to determine whether the in-house ELISA can be used as a seroepidemiological screening tool and/or stand-alone test for scrub typhus. A total of 1,976 admission and 1,438 participant follow-up sera collected in the Lao PDR (Laos) were tested with ELISA for IgM and IgG. Samples with an ELISA OD≥0.50 were tested with IFA for IgM and/or IgG. A strong positive relationship was present between ELISA ODs and IFA titers for admission IgM (r2: 0.70, p <0.005) and IgG (r2: 0.76, p<0.005), and for follow-up IgM and IgG (both r2: 0.76, p<0.005) samples. The best compromise between sensitivity and specificity for the ELISA OD cut-off is likely to be between 0.8-1.0 for IgM antibodies and 1.2-1.8 for IgG antibodies. These results demonstrate that the diagnostic accuracy of the MORU in-house scrub typhus group ELISA is comparable to that of IFA, with similar results as reported for the commonly used InBios Scrub Typhus Detect ELISA, validating the use of the in-house ELISA. The optimal ELISA cut-off would depend on the use of the test, and the desired sensitivity and specificity. Further studies are required to authenticate the use of these cut-offs in other endemic regions. This in-house ELISA has the potential to replace the imperfect IFA, which could ultimately reduce the burden of scrub typhus by improving the rate of scrub typhus diagnoses in endemic low-resource areas.